1982
DOI: 10.1080/00071688208447931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal energy and protein intakes on the incidence of malformations and malpositions of the embryo and time of death during incubation

Abstract: 1. Broiler parent stock were fed daily allowances of 1.88, 1.73 or 1.52 MJ apparent metabolisable energy (AME) per bird at two different daily protein intakes (27.0 and 21.3 g crude protein (CP) per bird from 21 to 64 weeks of age. 2. The decrease in hatchability that occurred on the high protein (27.0 g CP), low energy (1.52 MJ AME) allowance from 26 to 36 weeks of age was due to an increase in the percentage of dead embryos in the second week of incubation and an increase in the number of "pipped" eggs at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Research by Pearson and Herron (1980, 1982a demonstrated mat both hatchability and egg production must be considered when evaluating ME intake at a fixed protein intake, and research by showed that fertility as well as egg production and hatchability must be considered when evaluating the effects of added fat. It was obvious from the present data that increased ME intake from added fat was beneficial for egg productions.…”
Section: Table 5 Effect Of Four Levels Of Added Fat On Kilograms Of mentioning
confidence: 99%
“…Research by Pearson and Herron (1980, 1982a demonstrated mat both hatchability and egg production must be considered when evaluating ME intake at a fixed protein intake, and research by showed that fertility as well as egg production and hatchability must be considered when evaluating the effects of added fat. It was obvious from the present data that increased ME intake from added fat was beneficial for egg productions.…”
Section: Table 5 Effect Of Four Levels Of Added Fat On Kilograms Of mentioning
confidence: 99%
“…The dLys intake of 1,010 mg/hen per day in the semipurified diet was possibly higher than the optimum level and may have caused a higher percentage of late dead embryos, and perhaps, even a higher percentage of very early dead that were incorrectly classified as infertile eggs by candling and egg breakout. Pearson and Herron (1982) observed a decrease in hatchability when feeding breeders a lowenergy high-protein diet as a result of increased embryonic mortality in middle dead and unhatched pips. However, it is important to mention that most of the past research on the effects of CP on hatchability and embryo development is confounded by lack of information about amino acid content or other nutrients in the diet (Wilson, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…ADJANOHOUN (1993) comprovou que, de 2650 a 2700kcal EM kg -1 , os machos apresentaram melhor desempenho e fertilidade. PEARSON & HERRON (1982) demonstraram que a variação de 40% no conteúdo energético da ração interfere nos parâmetros de produção, já uma variação no consumo diário de proteína de 16,5g até 27g não compromete esses parâmetros.…”
Section: O Experimento Foi Conduzido Com O Objetivo De Avaliar Qual Ounclassified